Clinical Characteristics of Imported Cases of Coronavirus Disease 2019 (COVID-19) in Jiangsu Province: A Multicenter Descriptive Study. (29th February 2020) - Wu, Jian; Liu, Jun; Zhao, Xinguo; Liu, Chengyuan; Wang, Wei; Wang, Dawei; Xu, Wei; Zhang, Chunyu; Yu, Jiong; Jiang, Bin; Cao, Hongcui; Li, Lanjuan
Abstract: Background: We aimed to report the clinical characteristics of imported cases of coronavirus disease 2019 (COVID-19) in Jiangsu Province. Methods: We retrospectively investigated the clinical, imaging, and laboratory characteristics of confirmed cases of COVID-19 with World Health Organization interim guidance in 3 grade IIIA hospitals of Jiangsu from 22 January to 14 February 2020. Real-time RT-PCR was used to detect the new coronavirus in respiratory samples. Results: Of the 80 patients infected with COVID-19, 41 were female, with a median age of 46.1 years. Except for 3 severe patients, the rest of the 77 patients exhibited mild or moderate symptoms. Nine patients were unconfirmed until a third nucleic acid test; 38 cases had a history of chronic diseases. The main clinical manifestations of the patients were fever and cough, which accounted for 63 (78.75%) and 51 (63.75%) cases, respectively. Only 3 patients (3.75%) showed liver dysfunction. Imaging examination showed that 55 patients (68.75%) showed abnormal density shadow and 25 cases (31.25%) had no abnormal density shadow in the parenchyma of both lungs. Currently, 21 cases have been discharged from the hospital, and no patient died. The average length of stay for discharged patients was 8 days. Conclusions: Compared with the cases in Wuhan, the cases in Jiangsu exhibited mild or moderate symptoms and no obvious gender susceptibility. The proportion of patients having liver dysfunction and abnormal CT imaging was relatively lower than that in Wuhan. Notably, infected patients may be falsely excluded based on 2 consecutively negative respiratory pathogenic nucleic acid test results. Abstract : Compared with the cases in Wuhan, 80 imported cases of COVID-19 in Jiangsu Province exhibited mild or moderate symptoms and no obvious gender susceptibility, lower proportion of liver dysfunction, and abnormal CT imaging and higher frequency of nucleic acid detection.